Isolated Renal Metastasis from Neuroendocrine Tumor: How Rare is Rare? A Case Report and Review of the Literature - Irma Lengu; Santhi Ganesan (Journal of Urological Surgery)
Neuroendocrine tumors (NETs) are epithelial neoplasms arising from neuroendocrine cells that are widely distributed throughout the body. The kidney is a rare site for primary NETs and is even rarer as a metastatic site. We report an extremely rare case of a 58-year-old female with metastatic renal NET from a rectal primary without prior or concurrent liver metastasis. Diagnosis of NET of kidney can be challenging due to its rarity. Use of appropriate immunohistochemical markers and awareness of occurrence of these rare lesions in the kidney will enhance the diagnostic accuracy